From the Experience of Expert Assessment of Illegal Logging of Forest Stands - Irina A. Konovalova; Ekaterina V. Lelekova (Теория и практика судебной экспертизы)
The article presents the results of an expert assessment of the thinning out of forest stands on the territory of the N district of the Kirov region based on field studies. Fieldwork consisted of recalculating and measuring the diameters of stumps left after felling trees, establishing their species composition and quality condition to determine the volume of harvested wood in the context of species. The stumps found were identified as pine (70 %), spruce, birch, and aspen.The authors reveal that the release forest cutting was carried out within the boundaries of the designated cutting area with an excess of the established volume of wood harvesting for the prime breed (pine). The volume of felled pinewood exceeded 2.5 times; for other species, these data is more than 70 % lower than declared. At the same time, the total actual volume of the withdrawn wood does not exceed the data of the forest declaration. Based on the revealed violation of the forest legislation and the relevant regulatory documents, the authors have calculated the amount of damage caused to the forest plantation due to illegal logging of pine wood in the volume of 297 m3. The damage amounted to more than 4 million rubles.